Examining the Application of the Semi-Structured Interview Method in Public-Private Partnership (PPP) Infrastructure Studies - Ali Sunandar; Fitri Andriyanti; Saipol B. A. Karim; Umi K. Z Zulkifli (Institut Teknologi Sepuluh Nopember (ITS), 2026)
Public-Private Partnership (PPP) schemes are increasingly adopted to address infrastructure financing constraints and to support sustainable development objectives. In PPP infrastructure research, semi-structured interviews are widely used to capture in-depth perspectives from key stakeholders. Despite their extensive application, systematic understanding of how these interviews are designed, implemented, and reported remains limited. This study examines the application of semi-structured interview methods in PPP infrastructure research through a systematic literature review of studies indexed in the Scopus and Web of Science databases. The review evaluates research approaches, interview mediums, data collection and analysis techniques, software utilization, interview duration, participant selection criteria, sampling strategies, data saturation, and practices related to rigor and trustworthiness. The findings indicate that semi-structured interviews are predominantly employed within qualitative research designs and are frequently combined with thematic analysis and qualitative data analysis software. Face-to-face interviews and purposive sampling of experienced PPP stakeholders emerge as the most common practices. However, the review also identifies notable inconsistencies in the definition and reporting of data saturation and qualitative rigor across studies. This study contributes to methodological advancement by providing a structured overview of current practices and highlighting areas where clearer and more consistent reporting is required. The findings offer practical guidance for researchers and practitioners seeking to strengthen methodological rigor and transparency in PPP infrastructure research.